IMPETIGO KONTAGIOSA BERAT PADA ANAK DENGAN ATOPI: LAPORAN KASUS DENGAN TINJAUAN FARMAKOLOGI - Adelia Hanarizky Kurniasari; Dwiana Savitri (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2025)
Impetigo is a superficial pyoderma caused by bacterial infection confined to the epidermis and is highly contagious, particularly among children under five years of age. It presents in two forms: bullous and non-bullous (contagious) impetigo. Severe cases in children with atopic dermatitis are rarely reported, although atopy increases susceptibility to infection due to impaired skin barrier function and alterations in the skin microbiome. The patient was hospitalized for five days under daily clinical observation and laboratory monitoring. Treatment included intravenous ampicillin–sulbactam, systemic dexamethasone, a topical fusidic acid–betamethasone combination, and 0.9% NaCl compresses were applied to the lesions. A two-year-old girl with a history of atopy presented with extensive, foul-smelling yellowish pus covering the entire scalp, accompanied by severe pruritus and pain. Yellow-brown crusted impetigo lesions were also observed across the body. Laboratory evaluation revealed mild leukocytosis with neutrophil predominance, and Gram staining demonstrated numerous Gram-positive cocci (+++). The therapeutic strategy aimed to control infection, suppress inflammation, and accelerate healing through a rational pharmacotherapeutic approach in accordance with CDC (2025) and IDSA (2014) guidelines. Dosage, duration, and adverse effects were collaboratively monitored by physicians and clinical pharmacists, accompanied by family education on hygiene and skin care to prevent recurrence. After five days of treatment, significant clinical improvement was observed, including reduced exudate, crusting, and pruritus. This report highlights the importance of comprehensive and collaborative pharmacotherapeutic approach and identification of recurrence risk factors in severe contagious impetigo with atopy to optimize treatment outcomes and patient quality of life.